2015
DOI: 10.1098/rspb.2015.1292
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual expertise in forensic facial image comparison

Abstract: Forensic facial identification examiners are required to match the identity of faces in images that vary substantially, owing to changes in viewing conditions and in a person's appearance. These identifications affect the course and outcome of criminal investigations and convictions. Despite calls for research on sources of human error in forensic examination, existing scientific knowledge of face matching accuracy is based, almost exclusively, on people without formal training. Here, we administered three cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
337
5
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(371 citation statements)
references
References 34 publications
28
337
5
1
Order By: Relevance
“…Facial identification methods have been validated through empirical studies and found to be accurate (White et al, 2015).…”
Section: Digital/multimedia Evidencementioning
confidence: 99%
“…Facial identification methods have been validated through empirical studies and found to be accurate (White et al, 2015).…”
Section: Digital/multimedia Evidencementioning
confidence: 99%
“…Cam1-2, Cam3-4, Cam5-6) is reported. In particular, at first, the comparison of all uncertainty components involved in (4) and (5) is made. Then, the recognition performance of the systems is presented by comparing suitable figures of merit, typically adopted for the analysis of classification systems [40].…”
Section: Performance Comparisonmentioning
confidence: 99%
“…Moreover, FR systems exploit digital images and photogrammetry to provide contact-less identification [2], [3]. Those systems spread widely due to an increasing demand in the fields of security assurance and automatic identity verification [4] - [6]. In fact, it is possible to find applications showing good performances and good maturity [7] when operating under constrained conditions, so that the person to be identified lies in a controlled environment and faces the camera(s) with a specified orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Fingerprint examiners are also more accurate than novices at discriminating briefly presented prints, although their performance improves even more when given more time (Thompson & Tangen, 2014). Facial recognition experts show a similar advantage when matching briefly presented unfamiliar faces (White et al, 2015).…”
Section: Does Novel Object Expertise Rely On Memory?mentioning
confidence: 73%
“…prints Thompson, Tangen & McCarthy, 2013), and particular groups of facial recognition examiners, whose task it is to compare unfamiliar faces for identity, also display superior performance compared to novices (White, Phillips, Hahn, Hill & O'Toole, 2015; although see White, Kemp, Jenkins, Matheson & Burton, 2014). These examiners face a formidable recognition task day to day.…”
Section: Novel Object Recognition In Forensic Sciencementioning
confidence: 99%